Al-arbaeen Al-boldniy for Ibin Asker Historical Study (Journal of the College of Education for Women, 2019)
Fortieth book is IbnAssaker mechanisms of modern books authored attention appeared amenable to the Messenger of Allah's will (Fife da upon h-d) in his emotional tempting scientists say despite his weakness and preached it save forty Hadith of year necessitated intercession and entering heaven eh Fife FA scientists 1940s h.g. Gae updated combines forty Hadith on a particular topic, authored destinations differed and collected and compiled, the first item in the 1940s that Abdul Rahman Abdullah ibn al-mubaarakmarvzishaikAssaker promised more than thirty workbook in this kind of composition topics varied between consolidation and conversations prove the Almighty Barry qualities, conversations provisions, worship, preaching, and of them only in writing to correct sind conversations when modern imams, and some of them mention high conversations attribution, and some of them mention long conversations. ShaikAssaker, who was rated at this type it is a forty forty sleepless in alawal replacement in due diligence in establishing the imposition of Jihad as well as 40 countries studied, which disclosed save capacity came through the trip's widespread, Whitlam shaikAssaker in writing mentioned forty Hadith about forty fortyforty city elder companion in 40 subject with interest in graduate study, as well as talks and isnaad is very weak book of geographical and historical magazine. And can no longer write who wrote funny layers if we take into account his interest in a specific layer they ageing layer and layer with companions he didn't translate to the companions or full translation ageing because this place somewhere else. As well as in his novel about ageing in various countries of the benefits of knowing the imams of the novel in the 16th century Hijri, and knowing their sheikhs and to h any shaikAssaker on some women and some sentimental but also recounted on ageing posed very little for him and for his.